The growth and color of guppy fish (Poecilia reticulata) fry fed with Artemia nauplius and microworm - Kurniawan, Idham; Helmiati, Senny (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
The purpose of the research is to determine giving Artemia nauplius and microworms affects the growth and color of guppy (Poecilia reticulata) fish fry. Three treatments were used in triplicates using a completely randomized design in this research. P1 (100% Artemia nauplius); P2 (50% Artemia nauplius and 50% microworm); and P3 (100% microworm) were the three treatments. Analysis of variance was applied to analyze the findings at a 95% confidence level. Further analysis is done using Duncan's Multiple Range Test if the results suggest a significant difference. The results showed that giving Artemia nauplius and microworms did not affect the survival rate of guppy fry. The provision of 100% microworms resulted in absolute growth based on weight and length of 0.12 ± 0.01 g and 1.26 ± 0.07 cm, respectively, specific growth rates based on weight and length of 6.24 ± 0.14%/day and 2.02 ± 0.08%/day, respectively. and the highest increase in color quality, which was 3.33 ± 0.12, so it can be concluded that the provision of 100% microworms resulted in increased growth and color quality in guppy fish fry .